Participant experiences in HIV cure-directed trial with an extended analytical treatment interruption in Philadelphia, United States - Andrea Bilger; Eion Plenn; Frances K. Barg; Katharine A. Rendle; William B. Carter; Andrea Lamour-Harrington; Nora Jones; Beth Peterson; John A. Sauceda; Pablo Tebas; Karam Mounzer; David Metzger; et al. (HIV Research & Clinical Practice)
Background A feature of HIV cure trials is the need to interrupt treatment to test the efficacy of experimental interventions—a process known as analytical treatment interruptions (ATIs). Objectives We report the experiences of participants after they completed an extended ATI. Methods From April to November 2022, we conducted post-ATI in-depth interviews with BEAT2 clinical trial (NCT03588715) participants who stopped ART while receiving an immunotherapy regimen. We used conventional content analysis to code the data. Results We conducted interviews with 11 Black/African American and three White/Caucasian participants (11 males, two females, and one transgender woman). The mean ATI was 38 weeks. Participants noted several significant experiences surrounding the interventions’ side effects, ATI, and returning to medication. Some participants had positive experiences with their ATI. Other participants were nervous during the ATI. Rising viral loads led some to feel a sense of failure. Although trial experiences were heterogeneous, participants unanimously had positive interactions with the clinical trial staff which facilitated their retention in the trial. Participants shared their experiences with the trial, including changes in expectations, experiences with experimental interventions and procedures, compensation as a measure of respect, effort, transportation, and effects of COVID-19 during the trial. Based on these results, we provide considerations for the conduct of future HIV cure-directed clinical trials involving ATIs. Conclusions Managing expectations, focusing on participants’ contributions, and providing support to reduce feelings of having failed the research team and/or the HIV community following viral rebound should be part of HIV cure trial design. Discussing the mental health impact of rebound during consent, distinct from risk, is needed. Continued efforts to understand how people with HIV experience ATIs will improve future designs of HIV cure clinical trials.